A NEW ASSOCIATION OF GUILLAIN BARRE SYNDROME IN A PATIENT WITH CENTRAL NERVOUS SYSTEM MELIOIDOSIS - Koh, Ewe Jin; Tan, Kah Nian; Chan, Zhi Wei; Wong, Hoy Yan Candice; Chin, Ming Lee; Lee, Tiong Chan (Journal of Ayub Medical College Abbottabad, 2023)
Burkholderia pseudomallei affecting the central nervous system has been extensively reported in the literature. However, combined central nervous system and peripheral nervous system involvement in melioidosis has never been reported. We report a 66-year-old man with diabetes mellitus who was diagnosed to have central nervous system melioidosis and developed acute flaccid quadriplegia. Nerve conduction studies and anti-ganglioside antibodies were consistent with Guillain-Barre syndrome. This case report highlights the importance to recognise the possibility of Guillain Barre syndrome complicating central nervous system melioidosis and stresses the urgency of early consideration of this complication, as early immunomodulatory therapy may hasten neurological recovery.